Use of SSRI and SNRI Antidepressants during Pregnancy: A Population-Based Study from Denmark, Iceland, Norway and Sweden. - Helga Zoega; Helle Kieler; Mette Nørgaard; Kari Furu; Unnur Valdimarsdottir; Lena Brandt; Bengt Haglund (PLoS ONE, 2015)
Background The purpose was to describe utilization of selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs), including trends in prevalence, characteristics of users, drug switching and changes in prescribed doses in a large group of pregnant women across four Nordic countries. Methods A drug utilization study based on linked individual-level data from the nationwide prescription- and medical birth registers in Denmark, Iceland, Norway and Sweden. The study population comprised all pregnancies in these countries, resulting in a live birth or stillbirth after gestational week 22 from January 1st 2008 to December 31st 2012 (N = 1 162 470). In addition to the main study drugs SSRIs and SNRIs, we included (concurrent) use of other antidepressants, antipsychotics, anxiolytics and hypnotics. Results A total of 38 219 (3.3%) pregnancies were exposed to SSRIs and 5 634 (0.5%) to SNRIs. Prevalence of SSRI and SNRI use varied by country (1.8% in Norway to 7.0% in Iceland). Use and prescribed dosages decreased with each passing trimester of pregnancy; prevalence was 2.7% at conception, and 2.1%, 1.7% and 1.3% respectively in 1st, 2nd and 3rd trimester. In 0.6% of pregnancies women filled a prescription before pregnancy and in every trimester. In one third of exposed pregnancies, women were also dispensed anxiolytics, hypnotics or sedatives. Conclusion Use of SSRI and SNRI use during pregnancy varied between the Nordic countries, but the overall prevalence remained low and relatively stable from 2008 to 2012. The low prevalence of use and high proportion of women who discontinue treatment in pregnancy raise questions about adequate treatment of depression in pregnant women.